Removal of phenols and methane production with coffee processing wastewater supplemented with phosphorous - Villa-Montoya, A. C. [UNESP] (2017)
This manuscript addresses the evaluation of the methane production and removal of organic matter and phenols from coffee fruits processing wastewater (CPW). The systems consisted of two serial upflow anaerobic sludge blankets (UASB1 and UASB2) and one sequential batch reactor (SBR). The organic loading rate (OLR) was increased from 3 to 6 g COD/L.d, and the hydraulic retention times (HRT) applied to UASB1, UASB2 and SBR were 60, 30 and 75 h, respectively. Similar OLRs were tested with raw CPW (tests 1 and 2) and CPW after the addition of Simple Super Phosphate (SSP) (tests 3 and 4). The COD removals in the two stages UASB + SBR were approximately 85 % in tests 1 and 3 and 88 % in tests 2 and 4. The total phenols (TF) removal ranged between 70 and 92 %. The highest bioenergy productivities were achieved in UASB1, i.e., approximately 0.33 and 0.70 L CH4/L.d with OLR of approximately 3 and 6 g COD/L.d. Although, the addition of SSP did not induce a superior methane production or TF removal, it promoted enabled a faster biomass growth after acidification time. SBR was tested with two cycles—cycle 1 with anaerobic + aerobic reactions (tests 1 and 2) and cycle 2 with anaerobic + aerobic + anaerobic reactions and lower sedimentation time (tests 3 and 4). Cycle 2 obtained higher COD and TF removal. The addition of SSP enhanced the SBR performance and increased between 13 and 24 % the TF removal.